GC MS Analysis and Antibacterial Activity of Myristica fragrans seed Extracts against Lower Respiratory tract pathogen Acinetobacter baumanii - Pushpa Rani, T.P.Kumari; S.K.SUNDAR; Amma, B. Vijayalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
This study is destined to evaluate the antimicrobial activity of Nutmeg (Myristica fragrans Houtt) seed extract against the lower respiratory pathogen (Acinetobacter baumannii). The extract was subjected to phytochemical detection which confirms the presence of alkaloids, terpenoids, flavonoids, phenols and quinones, with the exception of Phlobatanins. Â The seed extract was tested against sixteen isolates of Acinetobacter baumannii . The susceptibility of these isolates towards the seed extracts was compared with each other and the antibiotic (Meropenem) which was used a as a positive control. Results in the former showed that toulene, tetrahydrofuran and methanol extracts of the seed exhibited antibacterial activity against the bacterial isolates The bioactive components present in the methanol extract were also evaluated by GC-MS analysis and the analysis revealed the presence of thirteen compounds.The study concludes that the secondary metabolites present in the plant Â can be an indispensible source of anitimicrobial compounds. Keywords: Myristica frangrans, Acinetobacter baumannii, solvents, antibacterial activity